2002
DOI: 10.1074/jbc.m205615200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Is Exported from the Escherichia coliCytoplasm by CydDC, an ATP-binding Cassette-type Transporter Required for Cytochrome Assembly

Abstract: Assembly of Escherichia coli cytochrome bd and periplasmic cytochromes requires the ATP-binding cassette transporter CydDC, whose substrate is unknown. Two-dimensional SDS-PAGE comparison of periplasm from wild-type and cydD mutant strains revealed that the latter was deficient in several periplasmic transport binding proteins, but no single major protein was missing in the cydD periplasm. Instead, CydDC exports from cytoplasm to periplasm the amino acid cysteine, demonstrated using everted membrane vesicles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
112
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 65 publications
9
112
0
Order By: Relevance
“…Benzylpenicillin and Dithiothreitol (DTT)-These were conducted essentially as described before (26) except that DTT sensitivity was measured in disk diffusion assays. Filter-sterilized solutions (10 l) of the stated DTT concentration were pipetted onto sterile filter paper disks (5-mm diameter) that were laid on a lawn of bacteria prepared from an overnight culture.…”
Section: Assays Of Motility and Sensitivity Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Benzylpenicillin and Dithiothreitol (DTT)-These were conducted essentially as described before (26) except that DTT sensitivity was measured in disk diffusion assays. Filter-sterilized solutions (10 l) of the stated DTT concentration were pipetted onto sterile filter paper disks (5-mm diameter) that were laid on a lawn of bacteria prepared from an overnight culture.…”
Section: Assays Of Motility and Sensitivity Tomentioning
confidence: 99%
“…Recently, we demonstrated that an ABC-type transporter, CydDC, originally identified by its requirement for assembly of the cytochrome bd-type terminal oxidase of E. coli (23)(24)(25), is a transporter of cysteine outwards across the cytoplasmic membrane (26). Given the established roles of GSH in redox buffering in eukaryotic cells (7), we hypothesized that GSH is also a substrate of CydDC.…”
mentioning
confidence: 99%
“…2). In Escherichia coli the last two genes are required for the formation of active cytochrome bd (11,27) and encode an ABC transporter which was reported to catalyze the export of L-cysteine (25) and glutathione (26). Since C. glutamicum does not possess a proton-or sodium ion-pumping NADH dehydrogenase, only the cytochrome bc 1 -aa 3 supercomplex and cytochrome bd oxidase couple electron transfer to the generation of an electrochemical proton gradient.…”
mentioning
confidence: 99%
“…Studies demonstrated that Escherichia coli (E. coli) efflux cysteine to the periplasm by CydDC transporters to regulate the redoxs status of the periplasm. 15) The disturbance of the redoxs status in the periplasm in CydDC mutants supported this view. It has also been shown that plasma thiol levels are implicated in cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 86%